MARA: A Mobile-based Academic Reminder Application - Acuña, Christian Alexis A.; Sabili, Mark Anthony; Friginal, Frances Frangelico S. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose   – The Mobile-based Academic Reminder Application (MARA) is built to help users, and focuses on the students in Emilio Aguinaldo College – Manila to manage their scheduled class and assignment deadlines via their mobile smartphones. The application was built for an Android-based platform. The user only needs to update their schedule after getting logged into the system and list any important date for their assignment deadline to the system. Then, the system will give an alert to remind the user of the upcoming class and task deadline. Method – The System Development Life Cycle (SDLC) which is the waterfall model has been chosen as the methodology for this project that contains five phases. Results – The result of the discussion shows that the Academic Reminder Application receives positive feedback through usability testing that has been completed. A total of 30 students completed the usability survey and 46.7% of respondents strongly agreed that this application meets their satisfaction with interface, usability, and performance. Conclusion – With the help of the mobile reminder system, users can stay organized and on track by reminding them of upcoming deadlines, appointments, and other important events. By setting up reminders, they can ensure that they won't forget important dates and can plan time accordingly. Recommendations – Future work recommendation for this project is to make a sharing application tool in the system so that the user can simply share the application with their friends. Besides that, the application can engage with new technology, which uses Near-Field Communication (NFC) on the login page to easier for students to log into the system. Research Implications – An academic reminder system is a tool that can be used to send reminders to users about upcoming events or tasks. A personal reminder system might be used to remind a user about an upcoming appointment or deadline. Practical Implications – The application revolves around improved time management, organization, communication, and overall academic performance for students, while also providing valuable data and insights for educational institutions to enhance their educational processes. Social Implications – The system can help improve academic performance, reduce stress, promote equity, and foster a culture of responsibility and technological literacy. However, it's essential to address privacy and integration issues to ensure that the social impact remains positive and inclusive.